Translation Of Political Phrases - Ernazarova Nargiza Khidirovna (Genius Journals, 2022)
This article is devoted to the specifics of the translation of political terms in media. The relevance of the work is due to the fact that today, due to the increasing intensity of international relations, socio-political translation is one of the most popular translations. The volume of socio-political texts published annually, aimed at a foreign-language audience, is quite large and, with the growth of international contacts, continues to increase.
Keywords: Political Phrases; Political Terms; Socio-Political Translation; Popular Translations